Dissolution Method Development and Validation for Estimation of Noscapine Tablets - Vyas, Jigar; Solanaki, Jaydip; Daxini, Kapil; Vyas, Puja; Pal, Neha (Journal of Drug Delivery and Therapeutics, 2020)
A dissolution method was developed and UV spectrophotometry was developed for the evaluation of the dissolution of tablets containing 15 mg Noscapine .The dissolution medium 0.1 N HCl was found suitable to ensure sink conditions. USP Apparatus 2, 900 mL dissolution medium 45 minutes and 100 RPM were fixed. Dissolution profiles were generated at 10, 15, 20, 30; 45 min. Dissolution samples were analyzed with UV spectrophotometer at 213 nm. The UV method for determination of tablet was developed and validated. The method presented linearity (R2 = 0.999) in the concentration range of 1–9 μg/mL. The recoveries were good, ranging from 97.18% to 101.45%. The intraday and Interday precision results were 0.54% and 0.78% RSD, respectively. The developed dissolution test is adequate for its purpose and can be applied for the quality control of tablets. Keywords: Dissolution test; Noscapine; Tablets; UV Spectrophotometry method